SEJARAH TERBENTUKNYA KECAMATAN PANGARIBUAN KABUPATEN TAPANULI UTARA DAN PERKEMBANGANNYA DARI TAHUN 2005-2015 - Gultom, Darlis Samuel; ', Prof. Dr. Isjoni, M.Si; Melay, M.Hum, Drs. Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The establishment of an area is always needed in order to achieve good governance and services for people’s welfare in accordance with the ability of each area in the process of development and growth. Every region in the world certainly has its own history both in terms of the process of formation, naming and also the development of the area which is different from other areas so as to make it unique. As well as Pangaribuan Subdistrict in North Tapanuli Regency is an area that formed in the Ducth colonial period. The purpose of this research was to know the history of the formation of Tapanuli district Pangaribuan northern districts, to know the development of Pangaribuan Subdistrict in North Tapanuli Regency since 2005-2015, particulary in education and health, to know the supporting factors and hindering the development of Pangaribuan Subdistrict in North Tapanuli Regency, to know socio-economic circumstances and cultural district community Pangaribuan. The method used is the historical method, where data were collected through observation, interviews, literature study, and documentation. Data analysis was done by descriptive qualitative. The location of the research is Pangaribuan Subdistrict in North Tapanuli Regency. Time of research since proposal seminar up to thesis seminar. The results showed Pangaribuan Subdistricts predominantly inhabited by ethnic Batak Toba , which is unique is this area where there is no resident surnamed Pangaribuan found and the name of the place. This area had been there before foreigners enteneringthis area, after the arrival of foreign nations then began to set in 1906, the region as a subdistrict that is part of the department Onder Afdeeling Silindung which is part of Batak Afdeeling Landen. The development of education and health is sufficient, the main economic sector is agriculture and agricultural potential is still very adequate to be developed. Required for mental renewal and new innovations for the future progress in the future.Keywords: History, Subdistricts Pangaribuan, Development